Implementation of Islamic Religious Education Through Cultivating Religious Culture in Smp 21 Malang City - Hasanah, Fitrotul (Didaktika Religia, 2018)
The purpose of Islamic Education in public schools is not only to make students understand Islamic teachings, but also to make students carry out these teachings in daily life. It is on this basis that the research focused on the implementation of Islamic Education through planting religious culture in Middle School 21 Malang. This study aims to: 1) describe the implementation of Islamic Education in State Junior High School 21 Malang 2) describe the efforts to cultivate religious culture in State Junior High School 21 Malang and 3) describe the supporting and inhibiting factors in cultivating religious culture in State Junior High School 21 Malang. The researcher observed the implementation of Islamic Education through planting religious culture using observation, interviews and documentation. The results of this study indicate that 1) Islamic religious education is carried out based on the curriculum established by the Ministry of Education and Culture 2) the implementation of Islamic Education through planting religious culture through various types of religious activities carried out outside of school hours and creating environmental designs which reflects the religious atmosphere by installing Islamic displays in certain places in the school environment 3) Factors supporting the cultivation of religious culture are principals, students, teachers and employees, and parents. While the inhibiting factor is the lack of examples from the teacher and the leader, diversity in giving sanctions in the event of a violation and differences in the background of the parents which have an impact on the failure of the cultivation of religious culture at home.